Competitive markets, collective decisions and group formation - Gersbach, Hans; Haller, Hans (CESifo working papers, 2003)
We consider a general equilibrium model where groups operating in a competitive market environment can have several members and make efficient collective consumption decisions. Individuals have the option to leave the group and make it on their own or join another group. We study the effect of these outside options on group formation, group stability, equilibrium existence, and equilibrium efficiency.
Keywords: Arbeitspapier; Graue Literatur